The Capitalisation of CAP Payments into Land Rental Prices: A Panel Sample Selection Approach. (29th December 2017) - Guastella, Gianni; Moro, Daniele; Sckokai, Paolo; Veneziani, Mario
Abstract: The empirical literature suggests that farmland prices and rents capitalise agricultural subsidies and that the 2003 reform of the EU Common Agricultural Policy, which decoupled subsidies from production and attached them to land, may have increased the extent of the phenomenon. Employing a farm‐level dataset, the Farm Accountancy Data Network (FADN) for Italy, we investigate this issue while accounting for selectivity, endogeneity and unobserved individual heterogeneity. To understand the impact of the reform we compare the estimates of capitalisation rate for decoupled payments with those for coupled payments. After correcting for unobserved individual heterogeneity and selectivity, our results reveal no capitalisation of coupled payments and only limited capitalisation of decoupled area payments into farmland rents in Italy.